Characterization and Seed Priming Effect of Plant Growth Promoting Bacteria Isolated from Wild Cotton Rhizosphere - , Moanaro Ong, Rajkumar B. K., Preeti R. Parmar, H. R. Ramani, Meet Dobariya, Diya Patel, Dukare Nikhil (Archives of Current Research International, 2025)
The present investigation was undertaken to explore the untapped potential of the rhizospheric bacteria associated with wild cotton, Gossypium aridum. All the 13 isolated rhizospheric bacterial isolates were screened for ten parameters comprising plant growth promoting (potash, phosphorus and zinc solubilization; IAA and GA3 production) and plant protection (chitinase, cellulase, and protease production; siderophore and HCN production). Four rhizospheric bacteria viz., NAU-RPM-4, NAU-RPM-9, NAU-RPM-1 and NAU-RPM-11 of wild cotton species recorded statistically significant plant growth and protection activities and thus chosen to study their seed priming effect on early cotton seedling growth of cultivated cotton (G. hirsutum). Bacterial isolate NAU-RPM-1 and NAU-RPM-11 significantly improved the growth parameters such as germination percent, shoot length, root length, fresh weight of shoot, dry weight of shoot, fresh weight of root, dry weight of root and root-shoot ratio as compared to absolute control. However, seed biopriming with NAU-RPM-4 and NAU-RPM-9 isolates also improved the early seedling growth parameters but this improvement was comparable to control. NAU-RPM-1 and NAU-RPM-11 were further characterized using 16S rDNA technique and preliminary identified as Enterobacter mori NAU-RPM-1 and Bacillus cereus NAU-RPM-11, respectively. Our results highlight the importance of rhizosphere bacteria isolated from wild cotton species (G. aridum) in improving the growth and resilience of cultivated cotton, especially in the context of utilizing PGPR for long-term sustainable agricultural practices.